Handbook of fractional calculus with applications. - Baleanu, Dumitru; Bǎleanu, Dumitru; Lopes, António M. (De Gruyter Reference ;, 2019)
This multi-volume handbook is the most up-to-date and comprehensive reference work in the field of fractional calculus and its numerous applications. This seventh volume collects authoritative chapters covering several applications of fractional calculus in in engineering, life, and social sciences, including applications in biology and medicine, mechanics of complex media, economy, and electrical devices.